Use of Medicinal Plants in Grogol Village Community as an Alternative Treatment for Illnesses - Sylvia, Dina; Husain, Fadly (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2024)
Medicinal plants have been an important part of cultural heritage and community knowledge for generations. This study aims to determine the use of medicinal plants in urban environments, especially in Grogol Selatan Urban Village, South Jakarta. This research uses a descriptive qualitative approach by collecting data based on field observations in accordance with the object of research, interviews, and documentation. The results showed that there are still many people in Grogol Selatan Village who believe in traditional medicine and utilize various types of medicinal plants, such as Abrus precatorius, Clitoria ternatea, and Morinda citrifolia, to treat various diseases. The utilization of these medicinal plants is a motivating factor for the community to get used to the use of natural materials